2003
DOI: 10.1200/jco.2003.02.105
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes Toward Participation in Cancer Clinical Trials

Abstract: These results indicate that the primary problem with accrual is not the attitudes of patients, but rather that the loss of potential participants is the result of the unavailability of an appropriate clinical trial and the disqualification of large numbers of patients. The pool of willing patients is further reduced by the reluctance of some physicians to engage in accrual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
283
7
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(311 citation statements)
references
References 23 publications
19
283
7
2
Order By: Relevance
“…Studies have found that a common reason for patient ineligibility to available protocols is narrow eligibility criteria. 3,14,21,22,23,24 Trial eligibility attempt to satisfy two opposing criteria. On the one hand, eligibility must be sufficiently narrow to produce a treatment effect that is approximately consistent across the cohort.…”
Section: Understanding Barriers To Clinical Trial Participationmentioning
confidence: 99%
“…Studies have found that a common reason for patient ineligibility to available protocols is narrow eligibility criteria. 3,14,21,22,23,24 Trial eligibility attempt to satisfy two opposing criteria. On the one hand, eligibility must be sufficiently narrow to produce a treatment effect that is approximately consistent across the cohort.…”
Section: Understanding Barriers To Clinical Trial Participationmentioning
confidence: 99%
“…Despite these advances in cancer prevention and patient care, only about 3-5% of cancer patients participate in clinical trials. 1,2 Assuring diversity in clinical trial participation is a national priority. In 1993, the most recent amendment to the National Institutes of Health (NIH) Revitalization Act (Public Law 103-43), 3 mandated the inclusion of women and minorities in clinical research and government sponsored human subject research including clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that slightly less than one-third (32%) of Americans would be willing to participate in clinical trials if asked, and, an additional 38% would be inclined to participate if asked but had some questions or reservations. 1 Therefore, factors other than patient intent or willingness seem to impede participation in clinical trials. Some of the salient factors impeding participation in clinical trials include: being a racial minority; 2, 5-7 older age; 2, 5, 7-9 lower socioeconomic status; 2, 6, 7, 10, 11 lack of appropriate clinical trials and the disqualification of patients; 1 the reluctance of physicians to engage in accrual; 1,12 doctor-patient communications regarding clinical trials; 7, 10, 13 mistrust of academic institutions, research and the medical system; 6, 10, 12, 14-17 fear of negative effects; 11 lack of community and physician awareness and knowledge of clinical trials benefits; 10,11,18 lack of sufficient infrastructure (including oncologists and approved cancer programs) to support trials in community settings; 2 lack of researcher training in culturally appropriate patient concerns and communication methods; 13,17,19 certain historical factors; 14 lack of adequate support for community outreach; poor access to care; 12 and lack of information on available trials.…”
Section: Introductionmentioning
confidence: 99%
“…Many share the responsibility to advance knowledge. The patients themselves are the least to blame; 'after appropriate information about a trial they generally accept participation, including randomization' (41). Actually, there has been a trend among patients to ask for a trial, recognizing that trial participation may mean that you get a better treatment than in routine care (42).…”
Section: Who To Blame?mentioning
confidence: 99%